Les Canadiens français, l'histoire et la démocratie: l'interprétation de Pierre Elliott Trudeau - Ouellette, Mélanie (Mens, 2000)
issued: 2000-23-00
Keywords: Trudeau; Pierre Elliott

Les signatures amérindiennes: essai d’interprétation des traités de paix de Montréal de 1700 et de 1701 - Guillaud, Yann; Delâge, Denis; D'avignon, Mathieu (Recherches amérindiennes au Québec, 2001)
Number: 2
Keywords: Autochtones; Français; Grande Paix de Montréal

Analyse et interprétations du génocide rwandais: nouveau fondement identitaire pour des rescapés du génocide dans la diaspora rwandaise de Montréal - Payette, Dominique (Université du Québec à Montréal, 2003)
Keywords: Rwandais

Notre Oscar Peterson est à New York - P. Boulianne, Sandria (Les médias parlent et chantent. Chroniques de la vie culturelle à Montréal durant la crise et la guerre, 2018)
Keywords: Musicien; Musique; Noirs

El teatro Playback: talleres de improvisación teatral para la integración de los inmigrantes latinoamericanos en Montreal - Barreto, Gaby (Université de Montréal, 2008)
Keywords: Latino-Américains; Théâtre

L'École littéraire de Montréal et la vie musicale - Lefebvre, Marie-Thérèse (La Vie culturelle à Montréal vers 1900, 2005)
Keywords: Musique; École littéraire de Montréal

Toot Sweet: When Jazz Ruled Montreal - Reynolds, Mark (The Beaver, 2001)
issued: 2001-06/2001-07
Keywords: Musique; Noirs

Les Noirs et le jazz au Québec - Lelièvre, Denys (Cap-aux-Diamants, 2004)
issued: 2004-23-00
Keywords: Musique; Noirs

La scène musicale anglo-québécoise: institutionnalisation, mutations et représentations - Robineau, Anne (Recherches sociographiques, 2014)
issued: 2014-09/2014-12
Keywords: Anglophones; Musique

Crisis? What Crisis?: Anglophone Musicmaking in Montreal - Stahl, Geoff (Université McGill, 2003)
Keywords: Anglophones; Musique

« Good-bye Broadway, Hello Montréal » Traduction, appropriation et création de chansons populaires canadiennes-françaises dans les années 1920 - P. Bouliane, Sandria (Université Laval, 2013)
Keywords: Anglophones; Canadiens français; Chanson; Francophones; Musique; Traduction

Le Black Theatre Workshop de Montréal: un nouveau bilan - Bayne, Clarence (L'annuaire théâtral, 2001)
issued: 2001-21-00
Keywords: Noirs; Théâtre

Memoria e riconoscimento nella narrazione filmica degli italiani di Montréal - Ramirez, Bruno (À l'italienne. Narrazioni dell'italianità dagli anni Ottanta a oggi, 2018)
Keywords: Cinéma; Italiens

Hair 1970. La tribu métissée du Québec - Lavertu, Yves (Éditions Yves Lavertu, 2020)
Keywords: Musique; Noirs; Théâtre

George M. Brewer et le milieu culturel anglophone montréalais, 1900-1950 - Huston, Lorne; Lefebvre, Marie-Thérèse (Septentrion, 2020)
Keywords: Anglophones; Francophones; Musicien; Musique; Théâtre

Une ville - plusieurs reels: Montreal’s Multicultural Irish Soundscape - Tétrault-Farber, Jérémy (Université Concordia, 2019)
Keywords: Irlandais; Musique

Statesman of the Piano: Jazz, Race, and History in the life of Lou Hooper - Mills, Sean; Fillion, Eric; Rochat, Désirée (McGill-Queen's University Press, 2023)
Keywords: Musique

Femmes de soir (théâtre); suivi de Contours: réflexion à partir du théâtre africain-américain - Amoni, Emmanuelle (Université du Québec à Montréal, 2000)
Keywords: Africains; Noirs; Théâtre

Influence de la culture hip-hop québécoise sur les adolescents montréalais d'origine haïtienne - Tessier, Karine (Université du Québec à Montréal, 2008)
Keywords: Danse; Haïtiens; Musique

Les images de presse de la crise des caricatures de Mahomet dans les quotidiens Libération et Le Devoir en février 2006 - Nevert, Lélia (Recherches sociographiques, 2015)
issued: 2015-01/2015-04
Keywords: Caricature; Devoir (Le)

Jazz, gender, historiography: a case study of the "Golden Age" of jazz in Montreal (1925-1955) - Blais-Tremblay, Vanessa (Unviersité McGill, 2018)
Keywords: Femmes; Musicien; Musique; Noirs

Plus fort! L'histoire de Madame Audet: pionnière du théâtre et de la radio québécoises, amoureuse de la langue française - Gold, Muriel (Bouquinbec, 2018)
Keywords: Enseignants; Langue; Radio; Théâtre

A Gift for Their Mother: The Saidye Bronfman Centre Theatre. A History - Gold, Muriel (Productions Miri, 2007)
Keywords: Juifs; Théâtre

Speak up! The Story of Mme Jean-Louis Audet: Pioneer of Quebec Stage, Radio and the French Language - Gold, Muriel (Bouquinbec, 2018)
OCLC: 1221004209
Keywords: Enseignants; Langue; Radio; Théâtre

La musique des Chiliens exilés à Montréal pendant la dictature (1973-1989). La création de musiques de la résistance politique et la réception des auditeurs dans l’exil - Jordán González, Laura Francisca (Université de Montréal, 2010)
Keywords: Chiliens; Musique

Spirited Commitment: The Samuel and Saidye Bronfman Family Foundation, 1952-2007 - MacLeod, Roderick; Abrahamson, Eric John (McGill-Queen's University Press, 2010)
OCLC: ocn531018298
Keywords: Bronfman (famille); Bronfman; Samuel; Juifs; Philanthropie; Théâtre

À la ville, à la scène, l'impact fondateur des immigrants français - Olson, Sherry (Études canadiennes/Canadian Studies. Revue interdisciplinaire des études canadiennes en France, 2019)
Keywords: Français; Théâtre

Le théâtre francophone à Montréal de 1855 à 1880: les causes d'un développement tardif - Laflamme, Jean (Maxime, 2005)
Keywords: Francophones; Théâtre

Le théâtre francophone à Montréal de 1855 à 1880: une institution qui tarde - Laflamme, Jean (Université de Montréal, 2000)
Keywords: Francophones; Théâtre

La poésie en langue des signes et ses usages à Montréal (1960-2017) - Daigneault, Catherine (Université McGill, 2018)
Keywords: Langue; Poésie; Sourds

"Empire" et "Nation" dans le regard du Montreal Star sur la scène dramatique francophone. Les chroniques de Samuel Morgan-Powell (1913-1953) - Huston, Lorne (Chroniques des arts de la scène à Montréal durant l'entre-deux-guerres. Danse, théâtre, musique, 2016)
Keywords: Anglophones; Francophones; Idéologies; Journalistes; Montreal Star; Théâtre

''Une grande fête canadienne'': les Autochtones et le programme Arts et culture des Jeux olympiques de Montréal - Bureau-Capuano, Mélissa (Les Cahiers d'histoire, 2016)
issued: 2016-23-00
Keywords: Autochtones

Trajectoires et subjectivités italo-québécoises : le processus identitaire de la deuxième génération tel que conçu par Marco Micone, Mary Melfi et Paul Tana - Hélie-Martel, Anaïs (Université de Montréal, 2016)
Keywords: Cinéma; Italiens; Langue; Roman; Théâtre

Sebben che siamo donne (Although we are Women): a Comparative Study of Italian Immigrant Women in Post-War Canada and Australia - Iuliano, Susanna (Université McGill, 2001)
Understanding the lives of Italian women who migrated to Canada and Australia in the post-war period is the goal of this thesis. Although governments assigned women secondary roles as dependants and 'followers' in the migration process, I argue that Italian women were central, not marginal, to the migration and settlement experiences of Italian immigrants. By placing Italian women front and centre of this study, I contribute to a small but growing body of work that challenges the male-centred perspective of most literature on Italian-Canadian and Italian-Australian migration and ethnicity. This thesis is structured within a feminist framework and uses interdisciplinary methods to gather and interpret quantitative and qualitative information about the lives of Italian immigrant women in post-war Canada and Australia. Using government and church archives, personal interviews, ethnic newspapers, legal documents, marriage registers and participant observer fieldwork, I explore three major themes. Firstly, I examine Italian immigrant women's understanding of power relations within their homes and workplaces. Rather than cast women as either passive victims or all-conquering heroines, I present the complexity of the sources of power and weakness in immigrant women's lives. I argue that Italian immigrant women had to cope with exploitation and disadvantage because of their class, gender and ethnic status. However, they responded to these challenges with resistance and resilience, and were able to affect change and wield power within certain constraints. Secondly, I compare the experiences of migration and settlement for Italian immigrant women in Canada and Australia and show how women's experiences were united by common gender concerns. I found overwhelming similarities between the family lives and work experiences of Italian-Canadian and Italian-Australian immigrant women, and in the government policies and programs that attempted to direct their migration and settlement in the post-war period. Finally, I examine how Italian immigrant women helped to construct what it means to be 'Italian' in post-war Canada and Australia. I show how gender roles assigned to, and chosen by, Italian-Canadian and Italian-Australian women, served as boundary markers for ethnic difference. Perceived differences in attitudes towards waged work, mothering, family responsibilities and sexuality were used by Italian immigrant women to distinguish themselves as members of an ethnic collective. Lien avec Montréal - bien expliqué dans l'intro
Keywords: Femmes; Italiens